Intra-arterial administration of adriamycin-loaded albumin microspheres for locally advanced breast cancer. - Doughty, J. C. (BMJ Group, 1995)
Regional chemotherapy is an attractive but underevaluated method of treating locally advanced breast cancer. We have combined two novel methods of targeting by delivering a single pulse of adriamycin-loaded albumin microspheres down a radiologically placed internal mammary artery catheter. A complete response was observed and prolonged local control achieved.